Exposure to Polyhexamethylene Guanidine Exacerbates Bronchial Hyperresponsiveness and Lung Inflammation in a Mouse Model of Ovalbumin-Induced Asthma - Lee, Seung-Hwa; Ahn, Jae-Rin; Go, Han-Na; Lee, So-Yeon; Park, Min Jee; Song, Kun Baek; Yoon, Jisun; Jung, Sungsu; Cho, Hyun-Ju; Lee, Eun; Yang, Song-I; Hong, Soo-Jong (Allergy, asthma & immunology research, 2021)
Humidifier disinfectants (HDs) exposure has now been associated with acute lung injury and pulmonary fibrosis; polyhexamethylene guanidine (PHMG) has been confirmed to cause severe lung inflammation and fibrosis in mice. Recent evidence also indicates that HDs exposure increases the asthma risk in children, but the underlying mechanisms remain unclear. We aimed to investigate the effects of PHMG exposure on asthma in mice and the potential underlying mechanisms. BALB/c mice were intranasally administered PHMG (0.1 mg/kg/day; 5 days per week) during 2 episodes of ovalbumin (OVA) sensitization and were then challenged with 1% OVA by inhalation. Bronchial hyperresponsiveness (BHR), inflammatory cell influx into bronchoalveolar lavage (BAL) fluid, serum total and OVA-specific immunoglobulin (Ig) E levels, and histopathological changes in the lung were analyzed. The levels of asthma-related cytokines and chemokines were assayed in the lung tissues to evaluate possible mechanisms. Exposure to PHMG following OVA sensitization and challenge significantly enhanced BHR, inflammatory cell counts in BAL fluid, airway inflammation, and total serum IgE levels in the asthma mouse model. In addition, the levels of chemokine ligand (CCL) 11 and serpine F1/pigment epithelium-derived factor (SERPINF1) were significantly elevated in the lungs of these mice compared to those in the control and OVA-treated only groups. Our findings suggest that PHMG can enhance the development of allergic responses and lung inflammation via CCL11- and SERPINF1-induced signaling in a mouse model of asthma.